Cross-modal signatures in maternal speech and singing - Trehub, Sandra E.; Plantinga, Judy; Brcic, Jelena; Nowicki, Magda (Frontiers in Psychology, 2013)
We explored the possibility of a unique cross-modal signature in maternal speech and singing that enables adults and infants to link unfamiliar speaking or singing voices with subsequently viewed silent videos of the talkers or singers. In Experiment 1, adults listened to 30-s excerpts of speech followed by successively presented 7-s silent video clips, one from the previously heard speaker (different speech content) and the other from a different speaker. They successfully identified the previously heard speaker. In Experiment 2, adults heard comparable excerpts of singing followed by silent video clips from the previously heard singer (different song) and another singer. They failed to identify the previously heard singer. In Experiment 3, the videos of talkers and singers were blurred to obscure mouth movements. Adults successfully identified the talkers and they also identified the singers from videos of different portions of the song previously heard. In Experiment 4, 6- to 8-month-old infants listened to 30-s excerpts of the same maternal speech or singing followed by exposure to the silent videos on alternating trials. They looked longer at the silent videos of previously heard talkers and singers. The findings confirm the individuality of maternal speech and singing performance as well as adults’ and infants’ ability to discern the unique cross-modal signatures. The cues that enable cross-modal matching of talker and singer identity remain to be determined.